Review of the family Veliidae in Romania (Hemiptera: Heteroptera: Gerromorpha) - Berchi, Gavril Marius; Kment, Petr (Zootaxa, 2015)
A critical review of the family Veliidae (Hemiptera: Heteroptera: Gerromorpha) in Romania is provided. In total, two genera and eight species (Microvelia Westwood, 1834—3 species, Velia Latreille, 1804—5 species) are known from the country. Microvelia buenoi Drake, 1920 and Velia serbica Tamanini, 1951 are recorded for the first time from Romania. The occurrence of V. affinis filippii Tamanini, 1947 and V. mancinii mancinii Tamanini, 1947 is confirmed by additional records. Based on proven or suspected misidentifications, V. currens (Fabricius, 1794) and V. rivulorum (Fabricius, 1775) are excluded from the Romanian fauna. A checklist of the Veliidae of Romania and updated distribution maps are provided. Biogeographical aspects of the fauna are summarized.